IMPLEMENTASI GERAKAN LITERASI DIGITAL DI ERA BERKELIMPAHAN INFORMASI BAGI PENDIDIKAN TINGGI - Ahmad Iklil Saifulloh; Syihabul Irfan (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
The results of a survey conducted by the Ministry of Education and Culture, as many as 60 percent of teachers still have difficulty doing PJJ. In addition to health problems, the use of digital media that has not been optimal is a major obstacle. Many complaints from students who only get assignments without first explaining the material. The teachers only gave instructions through the WA group, only gave homework. Many e-learning platforms such as google class rooms only contain pdf and ppt. For researchers to overcome the problem of courageous education, it provides a little solution with a bold learning approach in poetry courses. By using a qualitative descriptive method, 10 bold materials are presented in the form of videos which will be the core material for the practice of making poetry directly with different approaches. The 10 videos are 1. Metaphor, 2. Simille, 3. Five Senses, 4. Literacy Foundation., 5. Anti Social Life, 6. Short and Long Term Memory, 7. Creative Writing with Formulas, 8. Unlimited, 9. Research, 10. Restrictions. From the ten videos, 10 poems were realized which later became the first Poetry Anthology to be printed and had an ISBN in the English Language and Literature Education Study Program, Faculty of Teaching and Education, Majapahit Islamic University with the title "Withut A Trace". Key Words: Digital Literacy Movement, Information in Abundance Era, Higher Education